Correlation of HER2/neu receptors and other prognostic factors in breast carcinoma - S., Srihari; A., John Amalan; D., Sivakumar; M., Gobinath (International Surgery Journal, 2018)
Background: Breast cancer is the most common malignancy and the leading cause of cancer related death among women all around the world. Evaluation of prognostic factors including biomarkers is highly recommended for the best management and therapeutic decision of breast cancer patients. Aim was to study the correlation of HER2/Neu receptors and other prognostic factors in breast carcinoma. Methods: Patients who are clinically diagnosed as carcinoma breast a detailed history will be taken. Patients were assigned TNM staging according to AJCC classification and posted for surgery than to find out the receptor status from that specimen. Results: In 60 cases, there is no significant correlation and association between the prognostic factors (age, menstrual status, tumour size, side of disease, nodal positivity, pathological subtypes, histological grading except ER receptor positivity PR receptor positivity) and HER2neu receptor positivity. Significant association noted between the HER2NEU receptor positivity and ER, PR receptor negativity. ER AND PR receptor status it shows that a significant proportion of PR receptor activation is independent on ER receptor activation. And also this independent PR receptor positive status give false positive results depends upon staining pattern ,transport method of tissue specimen. Conclusions: Our study results indicate the importance of ER, PR and HER-2/neu expression as prognostic factors for therapeutic decision.